An Interrupted Time-series Evaluation of the Association Between State Laws Mandating Prescriber Use of Prescription Drug Monitoring Programs and Discontinuation of Chronic Opioid Therapy in US Veterans. Issue 12 (December 2021) - Arnold, Jonathan; Zhao, Xinhua; Cashy, John P.; Sileanu, Florentina E.; Mor, Maria K.; Moyo, Patience; Thorpe, Carolyn T.; Good, Chester B.; Radomski, Thomas R.; Fine, Michael J.; Gellad, Walid F.
Abstract : Background: Most states have recently passed laws requiring prescribers to use prescription drug monitoring programs (PDMPs) before prescribing opioid medications. The impact of these mandates on discontinuing chronic opioid therapy among Veterans managed in the Veterans Health Administration (VA) is unknown. We assess the association between the earliest of these laws and discontinuation of chronic opioid therapy in Veterans receiving VA health care. Methods: We conducted a comparative interrupted time-series study in the 5 states mandating PDMP use before August 2013 (Ohio, West Virginia, Kentucky, New Mexico, and Tennessee), adjusting for trends in the 17 neighboring control states without such mandates. We modeled 25 months of prescribing for each state centered on the month the mandate became effective. We included Veterans prescribed long-term outpatient opioid therapy (305 of the preceding 365 d). Our outcomes were discontinuation of chronic opioid therapy (primary outcome) and the average daily quantity of opioids per Veteran over the following 6 months (secondary outcome). Results: We included 250 monthly cohorts with 225, 665 unique Veterans and 3.4 million Veteran-months. Baseline discontinuation rates before the PDMP mandates were 0.4%–2.7% per month. Kentucky saw a discontinuation increase of 1 absolute percentage point following its PDMP mandate which decreased over time. The other 4 states had no significant association between their mandates and change in opioid discontinuation. There was no evidence of decreasing opioid quantities following PDMP mandates. Conclusion: We did not find consistent evidence that state laws mandating provider PDMP use were associated with the discontinuation of chronic opioid therapy within the VA for the time period studied. Abstract : Supplemental Digital Content is available in the text.